ANALISIS NILAI KARAKTER YANG TERDAPAT DALAM FILM UPIN DAN IPIN PADA KEHIDUPAN SEHARI-HARI SISWA - Pratama, Gilang Aditya; Soegeng, Soegeng; Sukamto, Sukamto (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
There are many influences from watching Upin and Ipin films, ranging from educational moral messages to imitating the language contained in the film, namely Malay. The purpose of this study is to analyze the character values ​​in the film Upin and Ipin episode Taman Riang. The type of research used is qualitative with descriptive method. Methods of collecting data were interviews, listening, notes, questionnaires, and documentation. Based on the results of the research data analysis, it is found that the character values ​​in each scene of the Upin and Ipin film are found. The character values ​​found in Upin and Ipin film Taman Riang episode are religious, cooperative, hard work, honest, social care, curiosity, tolerance, respect for achievement, communicative/friendly and envious. The conclusion from the analysis of the Upin and Ipin films in the Taman Riang episode is that there are ten character values ​​contained in the Upin and Ipin films that can be used by teachers as media tools in the process of conveying character values ​​with a pleasant atmosphere.